Build Brand Resonance Through Brand Image and Brand Love (Study of Apple MacBook Users) - Lutfi Lutfi; Edi Rahmat Taufik; Hendra Hermawan (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This study aims to develop a basic theoretical model and a new empirical research model to close the gap between the results of a previous study and the results of the present study concerning the impact of Corporate Social Responsibility as perceived by a company on Brand Resonance.Methodology: This study employs descriptive and explanatory quantitative methods by administering an online survey to Apple MacBook users in the Facebook group MacBook Indonesia User. This study employed a non-probability sampling technique, the purposive method (purposive sampling) with a population of 1,328 individuals and a sample size of 151 individuals. Method for data analysis using Partial Least Square (PLS) and SmartPLS 3.2.9.Finding: 1) Perceived CSR has a negative but insignificant effect on Brand Resonance; 2) Perceived CSR has a positive and significant effect on Brand Image; 3) Perceived CSR has a positive and significant effect on Brand Love; 4)) Brand Image has a positive and significant effect on Brand Love; 5) Brand Image has a positive and significant effect on Brand Resonance; 6) Brand Love has a positive and significant effect on Brand Resonance. Additionally, Brand Image and Brand Love can moderate the relationship between Perceived CSR and Brand Resonance.Conclusion: Perceived CSR had a negative but not significant effect on Brand Resonance, a positive and significant effect on Brand Image, and a positive and significant impact on Brand Love. Brand Image had a positive and significant effect on Brand Resonance, a positive and significant effect on Brand Love, and Brand Love had a positive and significant effect on Brand Resonance.